2013
DOI: 10.4172/2161-0495.1000168
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrocurcumin Potentially Attenuates Arsenic Induced Oxidative Hepatic Dysfunction in Rats

Abstract: Arsenic (As) compounds are reported as environmental toxicants and human carcinogens. Exposure to arsenic imposes a big health issue worldwide. Tetrahydrocurcumin (THC) is an antioxidative substance, which is derived from curcumin, the component of turmeric. In view of this fact, the purpose of this study was to delineate the ameliorative role of THC against arsenic-induced hepatotoxicity in rats. In this context, we evaluated the mode of action of chronic oral exposure of sodium arsenite as the source of arse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…The activities of AST and ALT are sensitive indices of hepatic injury. Numerous studies have reported that elevated activities of AST and ALT in the plasma of arsenic-exposed rats are mainly attributed to cellular leakage and loss of functional integrity of hepatic membrane architecture [28,29]. Consistent with previous studies, we observed significantly higher levels of AST and ALT in rats exposed to arsenic than in control rats, probably resulting from hepatocyte membrane damage due to arsenic intoxication.…”
Section: Discussionsupporting
confidence: 91%
“…The activities of AST and ALT are sensitive indices of hepatic injury. Numerous studies have reported that elevated activities of AST and ALT in the plasma of arsenic-exposed rats are mainly attributed to cellular leakage and loss of functional integrity of hepatic membrane architecture [28,29]. Consistent with previous studies, we observed significantly higher levels of AST and ALT in rats exposed to arsenic than in control rats, probably resulting from hepatocyte membrane damage due to arsenic intoxication.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo studies demonstrated the potential protective effect of THC against chloroquine- and arsenic-induced hepatotoxicity [ 25 , 26 ]. The efficacy of THC on metabolic dysfunction was tested in streptozotocin-induced type 2 diabetic rats, decreasing levels of plasma insulin and gluconeogenic enzymes and improving blood glucose and hepatic carbohydrate metabolism [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This supports the observations reported 28,29 both As and Cd decreased body weight gain and food utilization and that these effects were more pronounced for the mixture. Available reports 30,31,32 also indicate that long term exposure to arsenic and cadmium could lead to significant reduction in body weights.…”
Section: Namentioning
confidence: 99%